Training on Making Modern Indonesian Herbal Medicine Products from Rhizome Plants as a Strategy to Increase Housewives’ Income in Johor Bahru, Malaysia - Rizal Koen Asharo; Nailul Rahmi Auliya; Vina Rizkawati; Elsa Lisanti; Raisyanggi Susta Mulyadi; Fadya Hidayatie; Mutiara Natalia Hotmauli Siahaan; Feby Aulya Ayu Wandira; Sandrina Chairunnisa (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract The training on making modern Nusantara herbal medicine products from rhizome plants aims to introduce Nusantara herbal medicine recipes with modern techniques while also having the potential to increase the income of housewives in Johor Bahru, Malaysia. This training focuses on introducing rhizome cultivation techniques, processing raw materials into herbal products, and marketing strategies to reach local and international markets. By implementing modern production methods and maintaining the efficacy of traditional herbal ingredients, participants are expected to be able to develop sustainable and profitable herbal medicine businesses. In addition, this training program also provides an opportunity for housewives in Johor Bahru, Malaysia to learn various practical aspects in the theory of processing and managing herbal medicine products so that they can support aspects of household-scale entrepreneurship and contribute to the family economy. Through this program, improvements in the quality of life and economic welfare of participants are expected to be achieved.